Ayurvedic Management of Primary Infertility Associated with PCOS - A Case Report (International Journal of Ayurveda and Pharma Research, 2023)
Poly cystic ovarian syndrome is a condition characterised by a wide range of signs and symptoms including menstrual irregularities, obesity, acne, hirsutism and is causing adverse effects on metabolic and endocrinal system. Exact etiology and pathophysiology is still unclear but it’s having a strong familial predisposition. This is a case report on an anovulatory infertility caused by PCOS. A 27-year-old female patient presented to the Streeroga OPD at ITRA On December 29, 2020, complaining of infertility, irregular and delayed menstruation, and weight gain over the past three years. She has been taking allopathic medicine for the same for the last two years. During her initial opd visit, she received a thorough medical history as well as all relevant clinical, physical, and laboratory tests. Bulky ovaries with polycystic morphology were discovered on sonography. Anovulatory factor infertility owing to PCOS was determined based on clinical symptoms and sonography. Pathadi choorna and Arogyavardhini rasa were chosen as medications and Samana oushadha was chosen as the line of management. The patient was counselled on lifestyle changes, the need of exercise, and correction of food habits. Patient was under medication for a period of 5 months. Patient got conceived after that and on 8th February 2022 she gave birth to a healthy male baby per vaginally with a baby weight of 3.2 kg.